Strategi Pemasaran Hijau: Bagaimana Kepercayaan Merek Memediasi Sikap Konsumen terhadap Merek Berkelanjutan - Ernesha Tierra Petronella; I Made Sukresna (Faculty of Economics and Business Diponegoro University, 2025)
The growing global awareness of sustainability has reshaped consumer preferences, urging companies to adopt environmentally friendly practices. This study examines the influence of environmental concern and green brand image on consumer attitude toward green brand, with brand trust as a mediating factor. Utilizing the Theory of Planned Behavior (TPB), this research investigates how consumer perception of sustainability impacts trust and positive attitudes toward brands that emphasize green initiatives.Data were collected from Apple users in Indonesia who have been exposed to Apple’s sustainability campaigns. A quantitative approach was applied, employing Partial Least Squares - Structural Equation Modeling (PLS-SEM) with SmartPLS 4 for data analysis.The results indicate that both environmental concern and green brand image significantly affect green brand trust, which in turn positively influences consumer attitudes toward green brand. Furthermore, green brand trust plays a critical mediating role in the relationship between environmental concern, green brand image, and attitude toward green brand.These findings highlight the importance of authenticity in corporate sustainability efforts. Companies should focus not only on building a strong green brand image but also on reinforcing consumer trust through transparent and verifiable sustainable practices. The study provides valuable insights for businesses aiming to strengthen their green marketing strategies and enhance consumer engagement in sustainability initiatives.